2004
DOI: 10.1002/mds.20157
|View full text |Cite
|
Sign up to set email alerts
|

Primary lingual dystonia induced by speaking

Abstract: We describe a 46-year-old woman who presented with lingual dystonia induced only by speaking, which responded well to anticholinergic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 6 publications
1
22
1
Order By: Relevance
“…The pathophysiologic mechanism of primary lingual dystonia induced by speaking remains unclear, and often the treatment of these patients is difficult. Some authors have suggested that anticholinergic medication, such as trihexyphenidyl, may be the treatment of choice in cases with lingual dystonia [1 2 3, 6]. In contrast to these cases, we observed that primary lingual dystonia may be intractable to anticholinergic treatment.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…The pathophysiologic mechanism of primary lingual dystonia induced by speaking remains unclear, and often the treatment of these patients is difficult. Some authors have suggested that anticholinergic medication, such as trihexyphenidyl, may be the treatment of choice in cases with lingual dystonia [1 2 3, 6]. In contrast to these cases, we observed that primary lingual dystonia may be intractable to anticholinergic treatment.…”
Section: Discussioncontrasting
confidence: 67%
“…One important feature of cases with lingual dystonia is responsiveness to sensory tricks [1, 2, 4, 5], for example, how chewing gum effectively relieved symptoms in our patient. However, this sensory trick only lasted for a few weeks, after which she experienced a gradual return of her symptoms.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…27 The technique is an intraoral injection performed by following the ramus of the mandible to locate the lateral ptyergoid and injecting approximately 45 units on each side. 28 For jaw closing dystonia, BoNT is injected into the masseter muscle. Palpation of the muscle at the angle of the mandible is performed and 20 units of BoNT are injected into each site.…”
Section: Oromandibular Dystoniamentioning
confidence: 99%